Analisis Tingkat Kepuasan Penumpang Berdasarkan Kinerja dan Fasilitas Pelayanan Stasiun Kereta Api Ngawi - Ependi, Ahmad; Kurniawan, Safrudin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to analyse the level of passenger satisfaction based on the performance and service facilities of Ngawi Railway Station. Passenger satisfaction is an important indicator in evaluating the quality of rail transportation services and understanding passenger needs. This study used a survey method with a questionnaire as a data collection tool. The sample was taken from passengers who use train services at Ngawi Station. The questionnaire focused on the minimum service standards for the transportation of people by train in Ministerial Regulation Number 63 of 2019. The collected data were analysed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods to identify the main variables contributing to passenger satisfaction.  This study's results indicate that visitors' satisfaction level with Ngawi Station with the Minimum Service Standards is very satisfactory, with an average percentage of 91.80%.